DIGITAL MEDIA AND LINGUISTIC IDENTITY: THE TRANSFORMATION OF YOUTH COMMUNICATION IN THE AGE OF SOCIAL MEDIA (Eureka Journal of Language, Culture & Social Change, 2025)
This study explores how social media platforms have reshaped linguistic identity among youth in multilingual societies. It investigates the blending of native languages with global digital discourse, resulting in hybrid linguistic practices such as “digital code-switching.” The research employs mixed methods, including discourse analysis of online communication and interviews with multilingual university students. Findings reveal that digital platforms act as linguistic ecosystems where users negotiate identity, belonging, and creativity. The study highlights the sociolinguistic implications of digital expression and proposes a framework for understanding cultural-linguistic hybridity in online communication.
Keywords: Linguistic Identity, Social Media, Code-Switching, Digital Communication, Cultural Hybridity.